Penerapan Waste Management Pada Proyek Ruko Di Kota Palangka Raya - Willyam Fernando Yuel Tanggara; Veronika Happy Puspasari (Jurnal Basement : Jurnal Teknik Sipil, 2024)
Construction products are one of the markers of the progress of a nation's development. One of the construction products such as shophouses is a building generally built multi-storey has two functions, namely as residential and commercial trade. The construction sector is a significant sector to improve the economy. On the other hand, the construction sector is a major contributor to the negative impact on the environment due to the amount of waste generated. One of the efforts to reduce the negative impact of construction waste is waste management. The purpose of this study was to determine the application of waste management in shophouse construction projects in Palangka Raya City. The research method was carried out by distributing questionnaires to developers and owners who had and were handling shophouse construction projects in Palangka Raya City. This research data uses primary data obtained directly from respondents, then the data is analyzed to obtain the mean value and standard deviation and then ranked. The results of the analysis show that the dominant application of waste management is: Design and construction using materials according to standards, Storage of materials that are resistant to weather, and Optimization of material use